HEPATOPROTECTIVE ACIVITY OF THE ETHANOLIC EXTRACT OF DOG FRUIT RIND (Pithecellobium lobatum Benth.) - Panjaitan, Ruqiah Ganda Putri; Savitri, Ely; Titin, Titin (Universitas Syiah Kuala, 2017)
The present study was conducted to investigate the hepatoprotective activity of ethanolic extract of dog fruit rind (Pithecellobium lobatum benth.) against carbon tetrachloride (CCl4) induced hepatotoxicity in rats. Male Wistar albino rats were randomly divided into four groups and administered orally with 50 mg/200 g body weight of dog fruit rind extract (K1), 100 mg/200 g body weight (K2) of dog fruit rind extract, 5 mg/200 g body weight of silymarin (K3/positive control), and 0.4 mL/200 g body weight of distilled water (K4/negative control), for seven days The levels of alanine transaminase (ALT) of each K1; K2; K3; and K4 were 143.4083.75 U/L, 94.8093.77 U/L, 130.2058.54 U/L and 147.25107.97 U/L, respectively, while the aspartate transaminase (AST) levels were 304.20128.67 U/L; 213.2088.93 U/L; 333.00128.31 U/L; and 239.25 94.90 U/L, respectively (P0.05). Group K2 showed better histological pattern than other groups with 60% of mild and 40% of moderate liver damage. Our findings revealed the hepatoprotective activity of the ethanolic extract of dog fruit rind.